Effects of a brief psychological intervention on students' sense of belonging and educational outcomes: The role of students' migration and educational background. (August 2019) - Marksteiner, Tamara; Janke, Stefan; Dickhäuser, Oliver
Abstract: Disadvantaged students who or whose parents immigrated (i.e., migration background) and first-generation students (i.e., non-academic background) have a higher risk of dropping out of school or university, earning poor grades, and facing mental health problems. This is likely in part a result of their impaired sense of belonging (e.g., feeling accepted and valued by peers and others) at educational institutions. In the current study, we tested the effectiveness of a belonging intervention that aims to reduce social disparities in sense of belonging—for the first time outside North America. Past research has demonstrated that the intervention supports disadvantaged students during the transition to middle school as well as to university. The intervention, at its core, is a brief reading-writing-exercise, which teaches that worries about belonging are common among freshmen and diminish over time. We conducted a pre-post-follow-up randomized control study with 86 freshmen (34.9% academic background, 44.2% non-academic background, 20.9% migration background). The intervention had differential effects on sense of belonging and self-reported grades after the first semester: For students without a migration background, the intervention had lasting positive effects on belonging; for students with a migration background, the positive effect diminished over time. Further, compared to students without a migration background, students with a migration background reported worse grades in the control condition and similar grades in the intervention condition. In addition, the intervention had positive—but no differential—effects on depression symptoms: students in the intervention group experienced less fluctuation and lower levels of depression symptoms than in the control group. The intervention had no significant effects on intentions to persist and emotional burden after six months. In sum, we found that the presented brief psychological intervention, adapted for the students with migration background, is effective but needs further customization to achieve positive and lasting outcomes.